Granulocyte colony stimulating factor versus human chorionic gonadotropin for recurrent implantation failure in intra cytoplasmic sperm injection: a randomized clinical trial - Mohamed Sobhy Bakry; Elsayed Eldesouky; Moatazza Mahdy Alghazaly; Elsayed farag; Eslam Elsayed Kamal Sultan; Hossam Elazzazy; Attia Mohamed; Soliman Mohamed Said Ali; Assem Anwar; Asmaa Ahmed Elrashedy; Mohamed Abdelmonem; Mohamed Abd-ElGawad; et al. (BMC Pregnancy and Childbirth)
Abstract Background Repeated implantation failure (RIF) is defined as the case whereby the transferred embryos fail to implant after several attempts of In vitro fertilization (IVF) which causes a profound impact on the quality of life and financial burden. Some clinical studies have confirmed that Granulocyte colony-stimulating factor (G-CSF) and human chorionic gonadotropin (HCG) can improve pregnancy outcomes and implantation rates. Hence, our study aims to compare the efficacy of G-CSF and HCG on pregnancy outcomes in RIF women who undergo intra-cytoplasmic sperm injection (ICSI). Methods This randomized, single-blinded study was conducted et al.-Azhar University Hospitals, Cairo, Egypt, between 10th October 2020 and 20th December 2020. The study included 100 women aged 20–43 years old undergoing ICSI cycles, with a history of RIF. Patients were divided randomly into two groups: group (1): included 50 patients injected with 500 IU of intrauterine HCG on embryo transfer day, and group (2): Included 50 patients injected with G-CSF on the embryo transfer day. Results In 100 RIF women, we found a significant improvement in pregnancy outcomes favoring G-CSF over HCG including implantation rate, chemical pregnancy, and clinical pregnancy (P < 0.0001, P = 0.0003, and P = 0.0006, respectively). Conclusion For the first time, we demonstrated a significant improvement in pregnancy outcomes favoring G-CSF over HCG in terms of implantation rate, chemical pregnancy, and clinical pregnancy. Trial registration The study was registered on Pan African Clinical Trials Registry with the following number: PACTR202010482774275 and was approved on 2nd October 2020.